P11 How drivers with brain pathologies deal with in-vehicle distraction, what are their emotions and driving habits: a questionnaire assessment. Issue 2 (June 2015) - Pavlou, Dimosthenis; Papantoniou, Panagiotis; Papadimitriou, Eleonora; Vardaki, Sophia; Economou, Alexandra; Yannis, George; Papageorgiou, Sokratis
Abstract: Background: Driving is a complex task, which requires possessing cognitive, motor and visual skills and it is necessary for the drivers to have adequate motor strength, speed and coordination. The normal ageing process leads to declines in these motor and cognitive skills, and when combined with a cerebral disease, it may significantly impair the person׳s driving performance, especially while being distracted. The objective of this paper is to analyze the self-reported driving behaviour of older drivers with brain pathologies, through an extensive questionnaire assessment. More specifically, the brain pathologies examined include Alzheimer׳s disease (AD), Parkinson׳s disease (PD), and Mild Cognitive Impairment (MCI) (some other cognitive diseases are included too). Two examined groups were asked to fill in the questionnaire: one "impaired" group and one "control" group. Methods: The questionnaire that was developed and used in order to compare impaired drivers with the healthy ones, includes questions about their driving experience, their usual driving routines, their self-assessment about their driving frequency and their possible avoidance of driving. The participants were also asked about their opinion about in-vehicle driver distraction (conversation with passenger or mobile phone use) and how they deal with it. Finally, they were asked about their emotions while driving. Within this framework, 140 drivers have participated in our research project, out of which 47 are healthy individuals (63.1y.o.±7.1) and 93 have some brain pathology (68.7y.o.±8.7). Results: The answers of the questionnaires were studied and analyzed by ANOVA techniques. Several statistically significant results were identified after the comparison of the two examined groups: Impaired drivers claim that their driving has been limited compared to 5 years ago, a lot more than control drivers. Moreover, they self-report, that they are likely to avoid using their vehicle because they are afraid of their driving abilities which they admit that have been deteriorated over the years. Regarding the distraction, there are significant differences too: impaired drivers find it too dangerous either to talk with a passenger or, even more, using the mobile phone and thus they avoid it. Drivers with brain pathology when conversing with mobile phone claim that they stop the vehicle. Then, they seem to be calmer than controls while driving, but on the other side, they use the seatbelt less. Conclusions: Drivers with brain pathologies are aware of their deterioration in their driving performance, and thus they are either very conservative while driving, or even they avoid doing so.